2014
DOI: 10.1155/2014/216039
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Derivations on Power Values of Lie Ideals in Prime and Semiprime Rings

Abstract: Let be a 2-torsion free ring and let be a noncentral Lie ideal of , and let : → and : → be two generalized derivations of . We will analyse the structure of in the following cases: (a) is prime and ( ) = ( ) for all ∈ and fixed positive integers ̸ = ; (b) is prime and (( V ) ) = ((V ) ) for all , V ∈ and fixed integers , , , , , ≥ 1; (c) is semiprime and (( V) ) = ((V ) ) for all , V ∈ [ , ] and fixed integer ≥ 1; and (d) is semiprime and (( V) ) = ((V ) ) for all , V ∈ and fixed integer ≥ 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Generalized derivations have been primarily studied on operator algebras. Therefore any investigation from the algebraic point of view might be interesting (see for example [7]and [8]).…”
Section: Introductionmentioning
confidence: 99%
“…Generalized derivations have been primarily studied on operator algebras. Therefore any investigation from the algebraic point of view might be interesting (see for example [7]and [8]).…”
Section: Introductionmentioning
confidence: 99%
“…Ashraf and Rehman [1] showed that a prime ring R with a nonzero ideal I must be commutative if it admits a derivation d satisfying either of the properties d(xy) + xy ∈ Z(R) or d(xy) − xy ∈ Z(R) for all x, y ∈ R. A number of generalizations of such kind of commutativity ideas found in [4,10]. Recently Rehman et al in [9] introduced a concept of multiplicative (generalized) -(α, β)derivations in rings as follows: A mapping G : R → R (not necessarily additive) is called multiplicative (generalized) -(α, β)derivation if there exists a map (neither necessarily additive or derivation) g : R→ R such that G(xy) = G(x)α(y) + β(x)g(y) for all x, y ∈ R. A mapping G : R → R (not necessarily additive) is called multiplicative (generalized) -(α, β) -reverse derivation if there exists a map (neither necessarily additive or derivation) g : R→ R such that G(xy) = G(y)α(x) + β(y)g(x) for all x, y ∈ R, where α and β are automorphisms on R.…”
Section: Introductionmentioning
confidence: 99%
“…Vincenzo De Filippis, Nadeem UR Rehman, and Abu Zaid Ansari [11] proved, let be a 2-torsion free ring and let L be a noncentral Lie ideal of R and let F : R −→ R and G : R −→ R be two generalized derivations of R, they analyze the structure of R in the cases:R is prime and R is semiprime ring after satisfy some conditions. In this notes we gave some results about the higher derivation (HD, for short) and Lie ideal of semiprime ring and prime rings.…”
Section: Introductionmentioning
confidence: 99%